Sticks, stones, fingers and bones: Nurturing knitting and the other neglected non-wovens - Malcolm-Davies, Jane (Archaeological Textiles Review, 2018)
Textile analysis is dominated by woven fabrics across all time periods. A variety of other textile production methods are attested by the archaeological and historical evidence, including knotting, lacemaking and sprang, and all are worthy of serious study. It is surprising to find knitted artefacts among these under-investigated textiles. The serious scientific study of evidence for early knitting is long overdue. Few knitted artefacts have been comprehensively reported leaving a large gap in the recorded history of textiles. This article sets out the argument for a new protocol to study knitted fabric and an agreed terminology for debating it.